Investigation of the Mode Structures of Multiphoton Induced Ultraviolet Laser in a ZnO Microrod - Guangping Zhu (Journal of Nanotechnology)
Hexagonal wurtzite structural ZnO microrods were fabricated by vapor-phase transport method. Under the excitation of a pulse laser with 1200 nm wavelength, the multiphoton induced ultraviolet (UV) laser was observed in a microrod. The dependence of the laser mode structures on pump intensity was investigated. The result indicates that the laser belongs to whispering gallery mode (WGM) at low pump intensity and Fabry-Perot (FP) mode at high pump intensity. The corresponding positive feedback mechanisms were discussed.